Bond and CDS Pricing with Credit Events - Trinh, Yen (Journal of Informatics and Mathematical Sciences, 2018)
A calibration methodology for default probability curves to bond and credit default swap (CDS) pricing is developed. Recovery of nominal (RON) policy and recovery of treasury (ROT) policy for the exposure at default (EAD) are considered for bond pricing. The paper presents the results of calculations of possible profit and loss (PnL) on bond portfolio and CDS portfolio.